LEGAL ANALYSIS OF THE IMPLEMENTATION OF RESTORATIVE JUSTICE TOWARDS CORPORATE RESPONSIBILITY IN THE CONTEXT OF ENVIRONMENTAL RESTORATION - Dadang Wahyudin; Diding Rahmat; Ardison Asri (JILPR Journal Indonesia Law and Policy Review, 2026)
This study discusses the legal analysis of the application of restorative justice to corporate accountability in the context of environmental restoration. Environmental violations committed by corporations generally have a widespread and serious impact on ecosystems and the lives of surrounding communities. In national regulations, environmental law enforcement can be carried out through administrative, civil, and criminal channels. One key point is that corporations, as legal entities, can be held criminally liable if proven to have caused environmental pollution or damage. However, the imposition of sanctions on corporations still faces various challenges, such as weak enforcement, interference from vested interests, and a lack of concrete restoration for the environment and affected communities. In line with this, the restorative justice approach has begun to gain attention as an alternative in resolving environmental disputes. This approach emphasizes restoring environmental conditions and fulfilling the rights of affected communities, rather than merely punishing the perpetrators. In the context of Law no. 32 of 2009, restorative justice is reflected in out-of-court dispute resolution mechanisms, mediation, and ecological restoration. However, the lack of strong technical and institutional guidelines limits its implementation. Therefore, there is a need to strengthen regulations and the commitment of law enforcement officials to apply restorative justice more effectively in order to create environmental law enforcement that is not only repressive but also solution-oriented and sustainable.